Pilasters at the back of the Mandapa - Temples of India Project Team (Jio Institute, 2024)
The pilasters at the back of the mandapa (pillared hall) are elegantly adorned with bell and chain motifs. At the centre of the mandapa, a stone sculpture of Nandi (Shiva’s bull) is placed, facing towards the garbhagriha (sanctum sanctorum).